Spatial Integration in Explaining the Accessibility to Residential Areas: Bandirma Case - H. Serdar Kaya; Elif Alkay (European Regional Science Association (ERSA), 2013)
In this research the topological accessibility values have been used as an alternative parameter for accessibility to examine whether any advantages to the evaluation of the socio spatial environment that are difficult to acquire with the geometrical distance measurement. The topological accessibility have been calculated via space syntax analysis which is called as ?spatial integration?. The basic principle of the space syntax methodology is based on the strict relationship between topological structure of urban environment and human behavior. In the space syntax method, the physical structure is represented as built space as a three dimensional objects such as buildings and non-built space as a base for movements in urban space. Topological structure itself affects the movement in space which is called as ?natural movement? and this relationship also affects the other sub systems such as land use, land values, etc. As the previous researches proves, topological structure and other urban systems are strongly correlated it is expected that spatial integration value should explain the spatial variations of physical environment. In this research this relationship analysed in Bandirma case in Balikesir province of Turkey. The analysis have been carried out with three factors based on spatial analyses and questionnaires of 795 households; the satisfaction from built environment, housing prices and Euclidean distances to the port, highways, city centre, seashore, schools, and industrial area. The first regression results show that there is a complex relationship between spatial structure and topological accessibility. According to the residual values, the spatial integration values through the main arterials fit better than the other areas of Bandirma. On the other hand, there are three distinct groups in the Bandirma case: The area near the main arterials, lately developed planned areas and old city structure. Comparing the last two areas show that spatial integration values in the old city structure are more meaningful in explaining the other factors than the newly developed areas. This difference may be the result of the difference between two types of spatial development reflecting the opposite perspectives which are bottom-up and top-down approaches. This research shows that the spatial integration values can be used as another variable to measure accessibility and this parameter may also help to explain the other features of spatial environment.
Keywords: 330; Space syntax; accessibility; Bandirma